Study of maternal mortality in a tertiary care hospital (GMERS-Dharpur, Patan, Gujarat, India): a three-year review - Jani, Parul S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Epidemiological data related to maternal mortality is valuable in each set up to design the progress to maternal mortality. This study was done to evaluate maternal death over period of 3 years at tertiary care centre of North Gujarat, India. Methods: This was retrospective study conducted at department of Obstetrics and Gynecology at GMERS medical college Dharpur, Patan (N.G.), India. Epidemiological data was collected from hospital register from January-15 to Dec-17 of maternal death in the hospital maternal age, parity, educational status, ANC registration, mode of delivery, admission death interval and direct and indirect causes and maternal deaths were noted and analyzed statistically. Results: There were 41 maternal deaths from Jan-15 to Dec-17. Maximum deaths were in 21-30 age group with multipara, unbooked and illiterate patients. Majority of maternal deaths are due to hemorrhage, eclampsia and sepsis. Conclusions: Many different factors interact in a complex way to increase the risk of death of pregnant women. Regular ANC, early identification of complication and timely referral, delivery by skill birth attendant and adequate post-partum case and follow up are required. To avoid maternal death unwanted pregnancy, too early pregnancy should be avoided adequate counseling and contraception facility also required for sepsis prevention, safe abortion services according to the law and quality post abortion care. There is a wide scope of improvement as most of the maternal deaths are preventable.